2022
DOI: 10.1037/pag0000701
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in specific and gist associative episodic memory across short- and long-term retention intervals.

Abstract: Age-related deficits in associative episodic memory have been widely reported, but recent research suggests that some of these deficits occur for highly specific but not gist representations. It remains undetermined whether older adults' deficits in specific associative episodic memory, observed in long-term memory, are also present in short-term memory. We used a continuous associative recognition task to address this question. Fifty young and 50 older adults studied face-scene pairs, with memory tests occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 93 publications
7
22
1
Order By: Relevance
“…In general, the results of this study may align with the previous literature on associative memory showing that age-related deficits are limited to the retrieval of specific representations (Greene & Naveh-Benjamin, 2020, 2022). The performance pattern in this study is also similar to that observed in SA patients in controlled retrieval tasks.…”
Section: Discussionsupporting
confidence: 90%
“…In general, the results of this study may align with the previous literature on associative memory showing that age-related deficits are limited to the retrieval of specific representations (Greene & Naveh-Benjamin, 2020, 2022). The performance pattern in this study is also similar to that observed in SA patients in controlled retrieval tasks.…”
Section: Discussionsupporting
confidence: 90%
“…Can older adults also remember the gist of associations when preexisting schematic support is likely to be less helpful? This question was addressed recently by Greene and Naveh-Benjamin (2020, 2022a; cf. Greene et al, 2022).…”
Section: Empirical Evidence On Age Differences In Memory Representationmentioning
confidence: 95%
“…Fuzzy-trace theory assumes that gist representations are more immune to decay and interference (Brainerd & Reyna, 1990, 2002, 2004), an assumption that has been supported in studies of narrative recall (Sekeres et al, 2016; Thorndyke, 1977). Nevertheless, gist representations likely also undergo some forgetting across time, as evident in recent studies with both young and older adults by Greene and Naveh-Benjamin (2022a, 2022b, 2023) showing losses across time not only of specific representations for associative memory but also in gist representations, albeit at a more protracted rate (i.e., losses in specific representations across time unfolded more rapidly).…”
Section: A Theoretical Framework For Future Researchmentioning
confidence: 97%
See 2 more Smart Citations